2015
DOI: 10.1111/jgs.13393
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Device Use in Older Adults and Incidence of Falls and Worry About Falling: Findings from the 2011–2012 National Health and Aging Trends Study

Abstract: OBJECTIVES To examine mobility device use prevalence among community-dwelling older adults in the U.S. and to investigate the incidence of falls and worry about falling by the type and number of mobility devices used. DESIGN Analysis of cross-sectional and longitudinal data from the 2011–2012 National Health and Aging Trends Study SETTING In-person interviews in the homes of study participants PARTICIPANTS Nationally representative sample of Medicare beneficiaries(N=7609). MEASUREMENTS Participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 20 publications
(47 reference statements)
6
84
1
6
Order By: Relevance
“…These devices can compensate for decrements in balance, gain mobility and overcome the fear of falling. It is noted that in 2011, 8.5 million U.S. seniors aged 65 and older reported having assistive walking devices, with a cane being most commonly used by two thirds of the elderly [17]. In this regard, the correct use of mobility devices becomes essential to guarantee optimal support and avoid postural deformities or physical impairments with the purpose of re-establishing a normal gait.…”
mentioning
confidence: 99%
“…These devices can compensate for decrements in balance, gain mobility and overcome the fear of falling. It is noted that in 2011, 8.5 million U.S. seniors aged 65 and older reported having assistive walking devices, with a cane being most commonly used by two thirds of the elderly [17]. In this regard, the correct use of mobility devices becomes essential to guarantee optimal support and avoid postural deformities or physical impairments with the purpose of re-establishing a normal gait.…”
mentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that provides de- 26 Canes (ie, walking sticks) have been reported as the most commonly used MD among people with a first-ever stroke, 27 middle-aged, and older adults with multiple sclerosis, 28 as well as among older adults in the United States 29 and Europeans. 30 These discrepancies suggest that people with PD require MDs with more support than other populations, but might also reflect that using a wheeled walker may be more advantageous than a cane for persons with PD.…”
Section: Discussionmentioning
confidence: 94%
“…Large differences in MD use in terms of age, education, income, ethnicity, and multimorbidity have been reported in previous studies involving older people. 29 Accordingly, such factors deserve attention in future studies on MD use in people with PD.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Assim, muitas vezes estes necessitam de recursos e auxílio de terceiros para a execução destas atividades, principalmente em relação à locomoção 17 . Porém, mesmo que estes idosos desenvolvam limitações físicas decorren-tes do acidente vascular encefálico, podem apresentar um melhor desempenho, se houver maior investimento em prevenção, promoção à saúde e reabilitação, dentro das instituições de longa permanência 18 .…”
Section: Resultsunclassified